The multilingual challenge for the construction and transmission of scientific knowledge - Berthoud, Anne-Claude; Gajo, Laurent (Multilingualism and diversity management, 2020)
"Whereas it is now generally recognised that multilingualism is important for society, culture and the economy, the relevance of multilingualism for the world of science has still largely escaped attention. But science, too, is created and transmitted in and through communication. Today, the construction and transmission of knowledge is based on a growing monolingualism, with English as the lingua academica regarded as a condition of the universality of scientific knowledge. However, this idea is based on the illusion that languages are transparent and that the modes of communication are universal. In this book, it is shown how multilingualism can open different perspectives and improve the quality of knowledge by offering an antidote to the squeezing out of different academic and scientific cultures. More precisely, it is shown how multilingual approaches highlight the mediating role of language and, in doing so, optimize conceptualization, communication and evaluation in science. These findings are, for one thing, relevant to institutional language policies and, for another, open new lines of research taking scientific practices themselves as a field of investigation"--